Immunohistochemical studies on the expression of cea, c-erbb-2 and cathepsin din tissue sections and fine needle aspirates of benign breast lesions - J, Hasnan; SS, Mutum; AM, Ismail (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2003)
The diagnosis of breast lesions in histopathology relies heavily on the morphology of the epithelial cells. This study aim at looking on the immunohistological expression of well-known prognostic markers ofbreast carcinoma i.e. CEA, c-erbB-2 and Cathepsin D on the epithelial cells of benign breast lesions in tissue sections and fine needle aspiration smears. Being strongly positive in malignant breast lesions, it is expected that the markers will be less positive or totally negative in beni~ epithelial cells. 91 cases of benign breast leSions composed of 46 cases of fibroadenoma, 18 cases of fibrocystic change, 10 ~ of sclerosing adenosis, 9 cases of epithelial hyperplasia, 7 cases of papilloma and 1 case of lactating adenoma were identified in tissue sections. CEA was positive in 11 of the cases (12%) and Cathepsin D was positive in 20 cases (22%). Complete ring of epimembranous cytoplasmic C-erb-B2 expression was absent in all the cases, therefore it is considered that all cases were negative for c .. erb-B2 expression. 13 cases (14%) comprising of9 fibroadenoma, 2 fibrocystic change and 2 epithelial hyperplasia showed incomplete ring of epimembranous staining by c-erb-B2. It appeare4 that CEA and c-erbB-2 expression is low in benign breast lesion and the expression is specific in the epithelial cells. However, CEA at the same time also showed strong positivity to the adjacent myoepithelial cells and this may give a higher result of positivity in such cases. For Cathepsin D expression, on top of showing strong positivity for myoepithelial cells and epithelial cells, it showed a non-specific positivity in the surrounding stromal cells. These findings indicate that c-erbB .. 2 and CEA rather than Cathepsin D are more likely to give a better distinguishing expression when comparing benign and malignant breast lesion in tissue sections. In 46 cases of fibroadenoma studied, CEA was positive in 10 cases (21. 7%) and Cathepsin Din 9 cases (19.6%). In 18 cases offibrocystic change studied, none showed expression for CEA and cerbB- 2 ; and 3 cases were positive for Cathepsin D. The same pattern is observed in sclerosing adenosis and papilloma cases studied. CEA and c .. erbB-2 were not expressed in 10 cases of sclerosing adenosis and 7 cases of papilloma. Cathepsin D was positive in 3 cases of sclerosing adenosis and 2 cases of papilloma Sl.cases of fine needle aspirates of benign breast lesion were also studied. 28·c~ compnsitig of 21 fibroadenoma, 4 benign proliferative lesion, 2 fibrocystic change and 1 non-specific · inflammatory lesion were subjected to CEA staining while another 23 cases ·comprising .of 18 . fibroadenoma, 3 beriign proliferative lesion, 1 :fibrocystic change and 1 non-specific inflammatory lesion were subjected to c-erbB-2 staining. For the CEA staining, 6· cases (21%) comprising of 5 fibroadenoma and 1 :fibrocystic change were positive. C-erbB-2 expression is only seen in one case ( 4%) out of 23 cases subjected to the staining and that single case was a fibroadenoma In the study of the fine needle aspirate, c-erbB-2 appears to be less expressed compare to CEA. · In conclusion, it can be seen that c-erbB-2 marker is significantly less expressed or not expressed at all compare to CEA in both tissue sections as well as in fine needle aspiration smears. Therefore c-erbB-2 marker is a potential tool that can be used to differentiate benign from malignant breast lesions. Cathepsin D due to its non-specific staining and increased background staining m.ake it unsuitable for usage to distinguish benign :from malignant breast lesions.